A combination of leaf rust resistance gene Lr34 and lesion mimic gene lm significantly enhances adult plant resistance to Puccinia triticina in wheat - Li, Tao; Bai, Guihua; Gu, ShiLiang (My University, 2012)
Leaf rust caused by Puccinia triticina is an economically-important disease in wheat worldwide. A combination of different types of resistance genes may significantly enhance rust resistance under rust-favorable conditions. To investigate the interactions between the rust resistance gene Lr34 and the lesion mimic gene lm on 1BL in Ning 7840, a segregating F8-10 population of 180 recombinant inbred lines was developed from Ning 7840/Chokwang and evaluated for both lesion mimic expression and leaf rust response at the adult plant stage in a greenhouse. A major quantitative trait locus (QTL), derived from Sumai 3, was co-localized with Lr34 on chromosome 7D and explained 41.5% of phenotypic variations for rust severity and 22.1% for leaf tip necrosis (LTN). The presence of Lr34 was confirmed by Lr34-specific markers cssfr1 and cssfr2 in Ning 7840 and Sumai 3. Unlike Lr34, lm conditioned a spontaneous lesion mimic phenotype and had a significant effect on reducing uredinial size, and a smaller effect on severity. Additive effects were observed between lm and Lr34 for severity and LTN, and an epistatic effect was observed for infection type. Single marker analysis also identified several other QTL with minor effects on severity, infection type, or LTN.
Citation: Li, Tao, GuiHua Bai, and ShiLiang Gu. “A Combination of Leaf Rust Resistance Gene Lr34 and Lesion Mimic Gene Lm Significantly Enhances Adult Plant Resistance to Puccinia Triticina in Wheat.” Chinese Science Bulletin 57, no. 17 (June 1, 2012): 2113–19. https://doi.org/10.1007/s11434-012-5001-x.
Keywords: Triticum aestivum; Puccinia triticina; Lesion mimic; Slow rusting gene Lr34; Leaf rust resistance